2021
DOI: 10.3390/v13071370
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Prion Infections Associated with Central Nervous System Syndromes in Brazil

Abstract: Virus-induced infections of the central nervous system (CNS) are among the most serious problems in public health and can be associated with high rates of morbidity and mortality, mainly in low- and middle-income countries, where these manifestations have been neglected. Typically, herpes simplex virus 1 and 2, varicella-zoster, and enterovirus are responsible for a high number of cases in immunocompetent hosts, whereas other herpesviruses (for example, cytomegalovirus) are the most common in immunocompromised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 252 publications
(342 reference statements)
0
14
0
1
Order By: Relevance
“…The most commonly detected herpesviruses in patients with neurological changes were HHV-6, CMV, and HHV-7. Although a statistically significant association between neurological changes and herpesvirus detection was only observed for HHV-6, CMV was also detected in several patients, and the reactivation of this virus is also associated with neurological changes in immunocompromised patients [ 20 ]. The immunosuppressive condition triggered by SARS-CoV-2 infection may play a role in reactivation herpesvirus, which may cause diffuse encephalitisand myelitis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly detected herpesviruses in patients with neurological changes were HHV-6, CMV, and HHV-7. Although a statistically significant association between neurological changes and herpesvirus detection was only observed for HHV-6, CMV was also detected in several patients, and the reactivation of this virus is also associated with neurological changes in immunocompromised patients [ 20 ]. The immunosuppressive condition triggered by SARS-CoV-2 infection may play a role in reactivation herpesvirus, which may cause diffuse encephalitisand myelitis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a statistically significant association between neurological changes and herpesvirus detection was only observed for HHV-6, CMV was also detected in several patients, and the reactivation of this virus is also associated with neurological changes in immunocompromised patients [ 20 ]. The immunosuppressive condition triggered by SARS-CoV-2 infection may play a role in reactivation herpesvirus, which may cause diffuse encephalitisand myelitis [ 20 ]. In addition, some patients were treated with corticosteroids, and we know that use of corticosteroids can trigger herpesvirus reactivation, studies have demonstrated the association between the use of corticosteroids and reactivation of CMV and HHV-6, which coincidentally also were the most detected herpesviruses in our study population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies about CNS infection have been conducted in recent years, and non-polio enteroviruses have mostly been reported as an important causative agent associated with sporadic cases and outbreaks [ 7 , 8 , 36 , 37 , 38 ]. In this context, we evaluated the epidemiological and molecular characteristics of CVB5 isolated from CNS infections between 2005 and 2018 in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ser extremamente raro no Brasil, no ano de 2017 foram relatados sete casos de GSS em duas famílias no país com mutação P102L, sendo quatro associadas a 129 M/V, dois a 129 M/M e um sem dado disponível para o códon 129. Estes indivíduos tinham idades entre 25 a 66 anos e tiveram um período de duração da doença variando entre 8 meses e 15 anos (Souza et al, 2021). Recentemente um caso de DCJ variante Heidenhain (sDCJ) foi relatado em uma mulher de 54 anos sendo este MM2C e cursando com alucinações visuais e progressiva e rápida demência (Mendonça et al, 2020).…”
Section: Epidemiologia Das Doenças Priônicas No Brasilunclassified